Reassessing Marital Rape Laws in India: A Study of Judicial Interpretations Legal Challenges and Medical Implications Under Bns, 2023 - Sheetal, Sheetal; Devi, Pratima (Journal of Neonatal Surgery, 2025)
The ongoing debate over the legal status of marital rape in India raises critical issues of gender equality, bodily autonomy, constitutional rights, and public health. India remains one of the few countries retaining the marital rape exception (MRE), even as numerous nations have criminalized non-consensual intercourse within marriage. The retention of this exception in the Bharatiya Nyaya Sanhita (BNS), 2023, which replaces the Indian Penal Code (IPC), 1860, has reignited discussions about women’s empowerment, legislative reform, and the broader societal and medical implications of marital rape. This article critically examines the evolution of marital rape laws in India, focusing on judicial interpretations and the legislative framework under the BNS, 2023. It conducts a comparative analysis of the rape provisions in the BNS and the IPC, evaluating their compliance with constitutional mandates, international human rights standards, and the urgent need to address the physical and psychological health impacts on survivors. Marital rape has significant medical consequences, including physical trauma, reproductive health issues, post-traumatic stress disorder (PTSD), depression, and other mental health conditions, which highlight the need for robust legal and medical interventions. The article further explores the challenges to criminalizing marital rape, such as concerns about the misuse of laws, societal resistance, and the potential implications for the institution of marriage. By incorporating judicial discourse, comparative legal analysis, and medical evidence, this research underscores the necessity of progressive reforms. Recognizing marital rape as a criminal offense is essential for achieving gender justice, protecting human rights, and ensuring holistic societal well-being